Care Perceptions in two ICU Nursing Care Delivery Models: A qualitative-comparative approach - López Cárdenas, William Iván; Henao Murillo, Natalia Andrea; Gil Vidal, Esteban; Altamirano Ceron, Rosa Milena; Santa Mejía, Yuly Andrea; Jurado Jiménez, Adriana Cristina (Investigación y Educación en Enfermería, 2023)
Objective. Analyzed in compared perspective perceptions about nursing care, nurse-patient interaction, and nursing care outcomes in two ICU nursing staff in a high-complexity hospital institution, whose Nursing are Delivery Models (NCDM) are differentiated by the proportion of nurses and nurse assistants (NA) per team and by the assigned tasks and responsibilities. Methods. Particularist ethnography with adaptation to virtual methodologies. It included the sociodemographic characteristics of 19 nurses and 23 NA, 14 semi-structured interviews, review of patients’ clinical records, and a focus group. Coding, categorization, inductive analysis, validation of results with participants were conducted and thematic saturation was achieved. Results. Four themes were identified: i) Professionalized care: a nursing of superior value; ii) senses and feelings of care; iii) nursing workload, generating factors and impacts; and iv) nursing missed care as concrete expression of the nursing workload. Conclusion. Compared nursing teams perceived nursing care in different ways, since it was experienced based on the assigned responsibilities and the possibilities of interaction with patients. Nursing care in the NCDM of the ICU with prevalence of direct bedside care by nurses with support from NA, it was perceived as holistic, comprehensive, and empathetic; whereas in the ICU with prevalence of delegated care to NA, it was related with administrative leadership and management of the ICU. Regarding the results, the NCDM of the ICU of direct bedside care by nurses showed better performance in patient safety and was closer to the skill level and legal responsibility of the nursing staff.